A Free trade area of the Asia-Pacific implications for the Philippine Agricultural and Food sectors - Rodriguez, U-Primo E. (2010)
This paper examines the effects of a Free Trade Area of the Asia-Pacific (FTAAP) on the Philippine agricultural and food sectors. Using a computable general equilibrium (CGE) model, it analyzes the impacts of removing tariffs on Philippine imports from members of the Asia-Pacific Economic Cooperation (APEC). It also evaluates the implications of exempting the agricultural sector from such changes. The simulation results suggest that agriculture as a whole is likely to benefit from the FTAAP. However, they also reveal potential losses for rice- and maize-related industries.
Keywords: Tariff; Tariff -- Philippines